Sustainable Ground Improvement Through Microbial Induced Calcium Precipitation -- A Review - Suriya, Pa.; Sangeetha, S.P. (Journal of Environmental Accounting and Management, 2026)
Microbial induced calcium precipitation (MICP) is one of the important emerging techniques in ground improvement. This technique is mainly based on Bio mineralization, which is the process of producing minerals (calcium carbonate) by living organisms called microbes. This technique is widely used in various fields such as biotechnology, geo technology, and also in paleo biology. Apart from the above applications, it is also used to remove the heavy metals, radio nucleotide, and atmospheric carbon dioxide sequestration. This paper reviews the approaches of various researchers on this technology applied for different types of soil such as clayey, silty soil, sandy soil and analyzed their optimum conditions to achieve their maximum shear strength. As well as, it is also discussing about the various influencing factors of microbial induced calcite precipitation like calcium concentration, dissolved matters of inorganic carbon concentration, pH of bacterial solution, and nucleation sites availability predominantly. As revealed from the literature reviewed the importance of the processing of bacteria at the optimum condition to adopt sustainable soil stabilization and various precipitations of polymorphs forms were effectively discussed. Though application of MICP and efficiency are required more to elevate in this technique for the field scale.